Downwash distribution of single-rotor unmanned agricultural helicopter on hovering state - Songchao, Zhang; Xinyu, Xue; Zhu, Sun; Lixin, Zhou; Yongkui, Jin (International Journal of Agricultural and Biological Engineering, 2017)
The effective coverage and velocity of downwash are directly related to the assemblage of spraying system and spraying effect. The downwash of the unmanned agricultural helicopter (UAH) N-3 was discussed in the paper. The computational fluid dynamics (CFD) methods were used to simulate and analyze the distribution of the downwash, and a wind field measurement device had been designed to test the downwash of UAH N-3. In the tests, the UAH N-3 was raised up to 5.0 m, 6.0 m and 7.0 m from the ground, “annular-radial-distribution- point” method was introduced, 8 directions separated by an angle of 45° (the radial direction) with the intersection point of the main rotor shaft and the ground plane as the center, 0.5 m as the step length for the longitudinal (to 2.5 m) and radial (to 4.0 m) direction to set the sample points, considering the range of the rotor rotating circular area mainly. The 5 m height results of N-3 were fully discussed to describe the downwash distribution with the longitudinal altitude increased and the radial distance increased. The standard deviations of five test altitudes for eight directions were comparatively analyzed, the results showed that the total standard deviation was not greater than 0.6 m/s. The overall relative maximum margin of error calculated from the simulation and measurement data was between 0.6 and 0.7, which verified the credibility of the simulation data. High-order polynomials were used to fitting the simulation and measurement data, the fitting results showed that the polynomial coefficient of determination R2 met or exceeded 0.75 when the altitudes were more than 1 m, indicating the fit equation having the reference values. When the altitudes equal or less than 0.5 m, the polynomial coefficient of determination R2 was smaller, ranging during 0.3 to 0.7. The study would provide some foundations for the optimization of the assemblage of spraying system on the single-rotor UAH, which would promote China aviation plant protection. Keywords: unmanned agricultural helicopter, single rotor, CFD simulation, downwash distribution, spraying effect DOI: 10.25165/j.ijabe.20171005.3079 Citation: Zhang S C, Xue X Y, Sun Z, Zhou L X, Jin Y K. Downwash distribution of single-rotor unmanned agricultural helicopter on hovering state. Int J Agric & Biol Eng, 2017; 10(5): 14–24.